1975
DOI: 10.1111/j.1399-3054.1975.tb03860.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Reactivity in Epidermal Cells of Begonia rex Excised and Grown in vitro

Abstract: Thin explants composed of the epidermis and underlying coUenchyma excised from leaf veins of Begonia rex and cultured in vitro are capable of neoformation of unicellular hairs, roots and buds. Unicellular hairs were formed over the entire surface of the explant when 10-^ M indole acetic acid or 10-'' M naphthaleneacetic acid (NAA) was added to the basal medium; each epidermal cell was potentially involved. The epidermis was most sensitive to a NAA treatment during the first few days of culture but 30% of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Explants excised from floral branches, composed of 3 -6 layers of epidermal and subepidermal cells, were capable of either flower or shoot bud formation. The system was also applied in shoot regeneration of Begonia rex [4], Torenia fournieri [3], Bryophyllum daigremontianum [1] and Psophocarpus tetragonolobus [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Explants excised from floral branches, composed of 3 -6 layers of epidermal and subepidermal cells, were capable of either flower or shoot bud formation. The system was also applied in shoot regeneration of Begonia rex [4], Torenia fournieri [3], Bryophyllum daigremontianum [1] and Psophocarpus tetragonolobus [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Tran Thanh Van 1980a). In monolayers of Begonia rex epidermal cells (Tran Thanh Van et al 1974, Chlyah andTran Thanh Van 1975) and in thin cell layers of tobacco (Tran Thanh Trinh 1978a, Tran Thanh Van 1980a, b) cultured under the same respective chemical conditions, it has been shown that unicellular hair differentiation and flower neoformation are affected by temperature and agar concentration, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…and 10 g/l agar, to which 1 µM BA was added for bud formation, or 0.5 µM NAA for root formation, or 0.1 µM NAA for unicellular hair formation. This new morphogenetic program, expressed after 6 days of culture, represents one of the simplest types of differentiation (Chlyah and Tran Thanh Van, 1975).…”
Section: Begonia (Begonia Rex) Over 2000 Species Of Begoniamentioning
confidence: 99%